Finding the Rhythm of Sudden Cardiac Death: New Opportunities Using Induced Pluripotent Stem Cell–Derived Cardiomyocytes - Sallam, Karim; Li, Yingxin; Sager, Philip T.; Houser, Steven R.; Wu, Joseph C. (Circulation research, 2015)
Sudden cardiac death is a common cause of death in patients with structural heart disease, genetic mutations, or acquired disorders affecting cardiac ion channels. A wide range of platforms exist to model and study disorders associated with sudden cardiac death. Human clinical studies are cumbersome and are thwarted by the extent of investigation that can be performed on human subjects. Animal models are limited by their degree of homology to human cardiac electrophysiology, including ion channel expression. Most commonly used cellular models are cellular transfection models, which are able to mimic the expression of a single-ion channel offering incomplete insight into changes of the action potential profile. Induced pluripotent stem cell–derived cardiomyocytes resemble, but are not identical, adult human cardiomyocytes and provide a new platform for studying arrhythmic disorders leading to sudden cardiac death. A variety of platforms exist to phenotype cellular models, including conventional and automated patch clamp, multielectrode array, and computational modeling. Induced pluripotent stem cell–derived cardiomyocytes have been used to study long QT syndrome, catecholaminergic polymorphic ventricular tachycardia, hypertrophic cardiomyopathy, and other hereditary cardiac disorders. Although induced pluripotent stem cell–derived cardiomyocytes are distinct from adult cardiomyocytes, they provide a robust platform to advance the science and clinical care of sudden cardiac death.